Fixed Point of Orthogonal F-Suzuki Contraction Mapping on O-Complete b-Metric Spaces with Applications - Ismat Beg; Gunaseelan Mani; Arul Joseph Gnanaprakasam (Journal of Function Spaces)
In this paper, we introduce the concept of generalized orthogonal F-Suzuki contraction mapping and prove some fixed point theorems on orthogonal b-metric spaces. Our results generalize and extend some of the well-known results in the existing literature. As an application of our results, we show the existence of a unique solution of the first-order ordinary differential equation.